Perancangan Web Design Untuk Meningkatkan Penjualan Di Warung Harian Rika - Lukmanul Hakim; Putri Nurul Lesmana; Muharrahmi; Alqori’ah Mardhatillah; Faradika (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The project to create the "Warung Harian" website is a response to the rapid development of information and communication technology, which has changed the business landscape significantly, especially for Micro, Small and Medium Enterprises (MSMEs). In this digital era, MSMEs need to adapt quickly to remain competitive and develop amidst increasingly fierce competition. Therefore, this project is aimed at helping the MSME "Warung Harian Rika" in utilizing digital potential in cyberspace. The aim of this project is to make a positive contribution by providing a solution in the form of a website that can expand the scope and increase the presence of "Warung Harian Rika" in cyberspace. The research methods used include exploring MSMEs, initial interviews with MSME owners, as well as a website design process that involves selecting content, appearance and features that suit the needs of "Warung Harian Rika". The result of this research is the creation of a website that can expand the reach and increase the visibility of "Warung Harian Rika". With this website, Warung Harian Serba Ada can more easily connect with potential customers, provide clear information about products and services, and provide an online shopping experience that makes it easier for consumers. It is hoped that this website can be an effective tool to introduce, promote and increase interaction between "Warung Harian Rika" and its potential customers.